α-Tocopherol nanodispersions: Preparation, characterization and stability evaluation. - Cheong, Jean Ne; Tan, Chin Ping; Che Man, Yaakob; Misran, Misni (Elsevier, 2008)
A top down approach based on emulsification–evaporation technique was used to prepare nanodispersion of α-tocopherol. Physicochemical properties of the prepared nanodispersions were investigated under combination of the processing parameters (pressure and cycle) and ratio of aqueous:organic. Storage study was performed for 3 months to evaluate the stability of all the prepared nanodispersions. The results showed that homogenization pressure have significant (P < 0.05) influence on the droplet diameter and size distribution. On the contrary, the processing cycle had not significant (P > 0.05) effect on the droplet diameter and size distribution of the prepared nanodispersion. Droplet diameters in the range of 90–120 nm were obtained for the prepared α-tocopherol nanodispersions. During storage duration, there were no significant (P > 0.05) changes in mean diameters while the concentrations of α-tocopherol were significantly (P < 0.05) reduced for all prepared nanodispersions. In general, it is shown that emulsification–evaporation technique can be used as a suitable technique for the production of α-tocopherol nanodispersions with narrow size distribution.